Microtubule Stabilization Enhances the Chondrogenesis of Synovial Mesenchymal Stem Cells - Li, Jiawei; Sun, Ziying; Lv, Zhongyang; Jiang, Huiming; Liu, Anlong; Wang, Maochun; Tan, Guihua; Guo, Hu; Sun, Heng; Wu, Rui; Xu, Xingquan; Yan, Wenjin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) are well known for their multi-directional differentiation potential and are widely applied in cartilage and bone disease. Synovial mesenchymal stem cells (SMSCs) exhibit a high proliferation rate, low immunogenicity, and greater chondrogenic differentiation potential. Microtubule (MT) plays a key role in various cellular processes. Perturbation of MT stability and their associated proteins was an underlying cause for diseases. Little is known about the role of MT stabilization in the differentiation and homeostasis of SMSCs. In this study, we demonstrated that MT stabilization via docetaxel treatment had a significant effect on enhancing the chondrogenic differentiation of SMSCs. MT stabilization inhibited the expression of Yes-associated proteins (YAP) and the formation of primary cilia in SMSCs to drive chondrogenesis. This finding suggested that MT stabilization might be a promising therapeutic target of cartilage regeneration.